2019
DOI: 10.1029/2019jb018139
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Sources of Seasonal Uplift in China Using Independent Component Analysis of GNSS Time Series

Abstract: With the improvement of Global Navigation Satellite System (GNSS) observation accuracy and the establishment of large continuously operating networks, long GNSS time series are now widely used to understand a range of Earth deformation processes. The continuously operating stations of the Crustal Movement Observation Network of China capture deformation signals due to time-dependent tectonic, nontectonic mass loading, and potentially unknown geophysical processes. In order to separate and recover these underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…In past decades, high-accuracy coordinate time series of global navigation satellite system (GNSS) stations have been widely used for monitoring seismic, coseismic displacements [ 1 , 2 ], and regional tectonic deformation [ 3 ]. The deformation signals, such as trend, annual and semiannual signals, as well as transit signals, can be detected from the GNSS time series, which contain abundant information from different sources, including tectonic and non-tectonic processes, such as the mass loading variations of snow, atmosphere and soil moisture [ 4 , 5 , 6 , 7 ]. The trend, annual and semiannual signals are usually estimated by the least-squares fitting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In past decades, high-accuracy coordinate time series of global navigation satellite system (GNSS) stations have been widely used for monitoring seismic, coseismic displacements [ 1 , 2 ], and regional tectonic deformation [ 3 ]. The deformation signals, such as trend, annual and semiannual signals, as well as transit signals, can be detected from the GNSS time series, which contain abundant information from different sources, including tectonic and non-tectonic processes, such as the mass loading variations of snow, atmosphere and soil moisture [ 4 , 5 , 6 , 7 ]. The trend, annual and semiannual signals are usually estimated by the least-squares fitting.…”
Section: Introductionmentioning
confidence: 99%
“…The other spatiotemporal signals are more effectively extracted and analyzed with some classic signal analysis methods, such as wavelet analysis (WA) [ 8 , 9 , 10 ], Kalman filter (KF) [ 11 , 12 ], empirical orthogonal function (EOF) [ 13 ], singular spectrum analysis (SSA) [ 14 , 15 ], and principal component analysis (PCA) [ 16 , 17 , 18 , 19 ]. Among these methods, PCA is one of the data-driven multivariate approaches based on second-order statistics (variance and covariance) and isolates the underlying sources without any prior knowledge [ 7 ], which implicitly assumes that a GNSS time series is polluted only by multivariate Gaussian noise. Nevertheless, previous studies demonstrated that a GNSS time series usually contains colored noise too [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to time variable characteristics of external environments and geophysical effects, GNSS position time series show significant seasonal changes, especially for the vertical component [8]. The main causes of seasonal oscillations are attributed to gravitational excitation, soil moisture and environmental loading variations [9][10][11]. If seasonal signals are not well characterized or there is non-random noise in the position time series, the velocity of a permanent station and its uncertainty will be misestimated [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Gruszczynska et al [ 30 ] used multichannel singular spectrum analysis (MSSA) to model the common seasonal signals in GPS observations in different regions around the world and without influencing the high frequency part of the spectra. Some other data-driven mathematical methods have been proposed to be used in modeling the geophysical signals from regional geodetic time series, e.g., principle component analysis (PCA) and independent component analysis (ICA), which have been widely used in smoothing and modeling GPS time series [ 15 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. ICA has especially been widely used in the separation of potential sources of seasonal signals in vertical GPS coordinate time series, and the main independent components (ICs) were thought to be consistent with some of the geophysical signals [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%